(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2025)
Teacher training, both initial and continuous, is a topic of great interest, especially when it comes to mathematics education. The various models that attempt to explain the knowledge necessary for teaching mathematics agree that it is necessary to have a thorough understanding of mathematical content and its relationships; specialized teaching knowledge; competence in the use of educational resources and technologies; and the ability to reflect on teaching practice. About early childhood mathematics education, research shows that a good mathematical foundation in childhood period predicts better future academic achievement. This highlights the need for solid teacher training, based on the latest educational research, which ensures not only knowledge of mathematics but also an understanding of how children learn. In this paper, we propose a holistic view of teacher training in Early Childhood Education, with initial training that provides basic tools for teaching mathematics and continuous training that encourages reflection, research on one’s own practice, and constant updating. We propose a continuous cycle of evaluation, reflection, and improvement that allows teachers to adapt to changing contexts and promote a more profound and meaningful approach to teaching mathematics to children.